10.4% Power Conversion Efficiency of ITO‐Free Organic Photovoltaics Through Enhanced Light Trapping Configuration. Issue 15 (26th May 2015) - Huang, Jiang; Li, Chang‐Zhi; Chueh, Chu‐Chen; Liu, Sheng‐Qiang; Yu, Jun‐Sheng; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> Highly efficient, indium tin oxide (ITO)‐free and flexible organic photovoltaic cells are demonstrated with 10.4% power conversion efficiency (PCE) through the innovative integration of ultrathin metal film electrode, conductive fullerene interfacial layer, and efficient active blend into a microcavity‐embedded device. In addition, a high PCE of 7.21% is achieved for the upsized devices with an active area of 1 cm2.